2023
DOI: 10.1210/clinem/dgad312
|View full text |Cite
|
Sign up to set email alerts
|

Malignancies in Prader-Willi Syndrome: Results From a Large International Cohort and Literature Review

Abstract: Context Prader-Willi syndrome (PWS) is a complex disorder combining hypothalamic dysfunction, neurodevelopmental delay, hypotonia, and hyperphagia with risk of obesity and its complications. PWS is caused by the loss of expression of the PWS critical region, a cluster of paternally expressed genes on chromosome 15q11.2-q13. As life expectancy of patients with PWS increases, age-related diseases like malignancies might pose a new threat to health. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 99 publications
0
1
0
Order By: Relevance
“…Additionally, a large study of 2561 British patients with constitutional autosomal deletions of chromosomal arms, confirmed the known association between deletion 11p and 13q with Wilms tumour and retinoblastoma, respectively, and identified that deletions of the genomic region 11q24 may predispose to anogenital cancer, in line with the recurrent somatic alterations described in these solid tumours [141][142][143]. Notably, several studies have reported cancer cases with other constitutional CNV such as Prader-Willi syndrome (deletion 15q11.2-q13) [144], DiGeorge syndrome (deletion 22q11.2) [145], Cri du Chat syndrome (deletion 5p) [146], and Williams-Beuren syndrome (deletion 7q11.23) [147], but their true incidence and any potential link with clinical outcomes remains unclear.…”
Section: Constitutional Cnv and Cancermentioning
confidence: 63%
“…Additionally, a large study of 2561 British patients with constitutional autosomal deletions of chromosomal arms, confirmed the known association between deletion 11p and 13q with Wilms tumour and retinoblastoma, respectively, and identified that deletions of the genomic region 11q24 may predispose to anogenital cancer, in line with the recurrent somatic alterations described in these solid tumours [141][142][143]. Notably, several studies have reported cancer cases with other constitutional CNV such as Prader-Willi syndrome (deletion 15q11.2-q13) [144], DiGeorge syndrome (deletion 22q11.2) [145], Cri du Chat syndrome (deletion 5p) [146], and Williams-Beuren syndrome (deletion 7q11.23) [147], but their true incidence and any potential link with clinical outcomes remains unclear.…”
Section: Constitutional Cnv and Cancermentioning
confidence: 63%